ATRIBUTOS FÍSICOS DO SOLO EM SISTEMA DE ROTAÇÃO DE CULTURAS COM BAIXA ENTRADA DE INSUMOS EXTERNOS - FERNANDES, SANDRA B. V.; BURATTI, JOÃO V.; FIORIN, CARLOS A.; QUADROS, VALMIR D. (Salão do Conhecimento, 2013)
Resumo